Flow Diversion - Vinall, Maria (MD Conference Express, 2011)
Endovascular treatment of aneurysms can be accomplished either by endosaccular occlusion using coils or liquid embolics or by parent vessel reconstruction using stents, alone or with coils. Although good for small, narrow-necked aneurysms, endosaccular occlusion with coils produces a low level of complete occlusion in giant (8.3%), large (21.1%), and small, wide-necked aneurysms (43.1%) [Fiorella et al. BNI-CCF Neuroform Database].